Mutations in the Gal83 Glycogen-Binding Domain Activate the Snf1/Gal83 Kinase Pathway by a Glycogen-Independent Mechanism - Wiatrowski, Heather A. (American Society for Microbiology, 2004)
The yeast Snf1 kinase and its mammalian ortholog, AMP-activated protein kinase (AMPK), regulate responses to metabolic stress. Previous studies identified a glycogen-binding domain in the AMPK β1 subunit, and the sequence is conserved in the Snf1 kinase β subunits Gal83 and Sip2. Here we use genetic analysis to assess the role of this domain in vivo. Alteration of Gal83 at residues that are important for glycogen binding of AMPK β1 abolished glycogen binding in vitro and caused diverse phenotypes in vivo. Various Snf1/Gal83-dependent processes were upregulated, including glycogen accumulation, expression of RNAs encoding glycogen synthase, haploid invasive growth, the transcriptional activator function of Sip4, and activation of the carbon source-responsive promoter element. Moreover, the glycogen-binding domain mutations conferred transcriptional regulatory phenotypes even in the absence of glycogen, as determined by analysis of a mutant strain lacking glycogen synthase. Thus, mutation of the glycogen-binding domain of Gal83 positively affects Snf1/Gal83 kinase function by a mechanism that is independent of glycogen binding.